TRADISI BUANG TETEMAS PERSPEKTIF PENDIDIKAN ISLAM - Zainuddin Zainuddin; M.Zakariya al Ansori; Muhammad Nurin; Jarir (Pascasarjana Universitas Hindu Indonesia, 2026)
The Buang Tetemas tradition is a form of local wisdom of the Malay community that still survives today, especially in the coastal areas of Kalimantan and Riau. This tradition serves as a symbol of self-purification from all forms of physical and spiritual disturbances and as an expression of gratitude to Allah SWT. This study aims to examine the Islamic educational values ​​​​contained in the Buang Tetemas tradition and its relevance to the development of contemporary Islamic education. The method used is library research by analyzing various literary sources such as Malay history books, scientific works, and the latest journals that discuss the integration of customs and Islam. The results of the study indicate that the Buang Tetemas tradition is in line with the concepts of tazkiyah an-nafs , thaharah , and ukhuwah Islamiyah . The values ​​​​contained in it reflect the spirit of togetherness, social concern, and physical and spiritual cleanliness all of which are part of the principles of Islamic tarbiyah. In the context of education, this tradition can be used as a local wisdom-based learning medium that teaches religious values ​​​​contextually and enjoyable. Furthermore, Buang Tetemas also plays a role in strengthening religious moderation by demonstrating how Islam can engage in dialogue with local cultures without losing the purity of its beliefs. This study concludes that preserving the Buang Tetemas tradition has significant potential to support the development of Islamic education that is humanistic, contextual, and rooted in national cultural values. Collaborative efforts between educational institutions, religious leaders, and traditional leaders are needed to integrate these traditional values ​​into Islamic curricula and learning practices that align with the principles of monotheism and morality.